P165 Vitamin D deficiency is associated with poor sleep quality in patients with Crohn's disease. (30th January 2023) - Walker, C; Stacey, W; Ramkalawan, K M; Kafienah, Y; Connaughton, R; Breslin, N; McNamara, D; O'Donnell, S; Ryan, B; O'Connor, A
Abstract: Background: Sleep disturbances affect 40-50% of patients with Crohn's Disease and are associated with disease flares. Symptoms, treatment side effects and pro-inflammatory status have been shown to have an effect on sleep quality and duration. Vitamin D deficiency affects between 18% and 70% of inflammatory bowel disease (IBD) patients and is independently associated with lower Health Related Quality of Life and greater disease activity. Our primary aim was to assess for a correlation between sleep quality and Vitamin D deficiency in people with IBD. Our secondary aim was to assess the impact of these factors on quality of life. Methods: 54 patients with Crohn's Disease were invited to attend for Vitamin D testing and complete a survey. Vitamin D deficiency was defined as a serum Vitamin D less than 30 nmol/L. The survey included general demographic information, inflammatory bowel disease information, Pittsburgh Sleep Quality Index (PSQI), disease activity score (Harvey Bradshaw Index), and the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). One-way ANOVA tests and unpaired t-tests were used to calculate the statistical significance. Results: · Median age 42.5 years. 50% female (n=27) and 50% male (n=27). · Mean duration of IBD was 17 years · 46% of patients were in clinical remission per HBI, 13% had mild activity, 37% moderate activity and 4% severe disease. · The mean global PSQI score was 7.7, with 61% (n=33) of participants having a global PSQI score >5, indicating poor sleep quality. · 24% of patients (n=15) had Vitamin D deficiency · Mean PSQI of patients with Vitamin D deficiency was 10.5 compared to 6.7 in those without (P= 0.008). Conclusion: Vitamin D deficiency is associated with poorer sleep quality in IBD, which in turn impacts quality of life in patients with IBD. IBD patients presenting with fatigue and sleep difficulties should be assessed for Vitamin D levels and treated where deficient.